PENGARUH MEDIA SOSIAL, HARGA, DAN KUALITAS JASA TERHADAP MINAT BELI PRIVATE TOUR JAKARTA GOOD GUIDE DI MASA PANDEMIK COVID-19 - Riky Ramadani Prabowo; Rahmat Ingkadijaya; Adhi Trirachmadi Mumin (Business Journal : Jurnal Bisnis Dan Sosial, 2023)
This study aims to determine (1) the influence of social media on service quality and purchase intention (2) the influence of price on service quality and purchase intention (3) the influence of service quality on purchase intention. (4) the influence of social media through service quality on purchase intention. (5) the influence of price through service quality on purchase intention. The purchase intention in question is the interest in buying the Jakarta Good Guide private tour during the covid-19 pandemic so that the tourism industry in the city can run bettter and the Jakarta Good Guide marketing strategy can be improved. The research product is Jakarta Good Guide’s private tour. This research was conducted by distributing questionnaires to 104 respondents who had participated in a regular walking tour program. The research method used is a quantitative method. The sampling technique used is simple random sampling method and processed by path analysis. The results show that there is no positive and significant influence of social media on purchase intention, there is a positive and significant influence of price on service quality, there is a positive and significant influence of social media on purchase intention, there is a significant influence of price on purchase intention, there is no positive and significant influence og service quality on purchase intention, there is no significant influence of social media on purchase intention through service quality and there is no significant influence of price on purchase intention through service quality.